Analysis of short-term clinical efficacy and immune function changes of advanced non-small cell lung cancer after radiotherapy or chemotherapy under CT-guided 125I seed implantation - Chen, Songbai; Kou, Yunfeng; Yuan, Yuting; Zhao, Guangsheng; Zhou, Jun; Wang, Ruoyu; Wang, Zhe; Li, Chuang (Frontiers in Oncology, 2025)
ObjectiveTo evaluate the clinical efficacy, safety, and changes in the immune status of advanced non-small cell lung cancer (NSCLC) patients with disease progression after chemoradiotherapy treated with CT-guided 125I radioactive seed implantation.Materials and methodsFrom January 2016 to June 2022, 34 NSCLC patients who progressed after radiotherapy and chemotherapy were studied retrospectively. There were 34 evaluable lesions, and 125I seeds were implanted into the lesions under CT guidance. The study’s endpoints were as follows: short-term clinical efficacy, quality of life score, and adverse reaction status assessment, with patients being collected for immune status assessment.ResultsThe average postoperative follow-up period was 16.58 ± 7.41 months. The 1-year postoperative survival rate was 76.47% (26/34), the 2-year postoperative survival rate was 58.82% (20/34), and the median overall survival was 16 (6–24) months (95% CI: 13.7–18.3). The 1-year progression-free survival (PFS) rate after the operation was 61.76% (21/34), the 2-year PFS rate was 41.18% (14/34), and the median PFS was 12.5 (1–24) months (95% CI: 10.8–16.2). Postoperative pneumothorax occurred in 11.76% of patients, minor bleeding in 5.88%, and pneumonia in 2.94%, all of which improved after symptomatic treatment. Compared with the preoperative results, the percentages of CD3+ and CD4+ T lymphocytes in the treatment group increased 1, 2, 3, and 6 months after surgery; the percentage of NK cells increased 3 and 6 months after surgery. The positive immune factor levels of IL-2 and TNF-α were increased at 2, 3, and 6 months after surgery; γ-IFN levels were increased at 1, 2, 3, and 6 months after surgery; IL-4 levels were decreased at 3 and 6 months after surgery; and IL-10 levels were decreased at 6 months after surgery. TH17 (IL-17) levels decreased at 1, 2, 3, and 6 months after surgery.ConclusionCT-guided 125I particle therapy may be an effective treatment for NSCLC that has progressed following radiotherapy and chemotherapy. Local treatments improve patients’ quality of life and reduce tumor burden. CT-guided 125I radioactive seed implantation may improve the immune status of patients with recurrent or progressive NSCLC after radiotherapy and chemotherapy and may enhance the antitumor immune response.